Excess purine degradation caused by an imbalance in the supply of adenosine triphosphate in patients with congestive heart failure. Issue 6 (December 1990) - Hisatome, I; Ishiko, R; Miyakoda, H; Saito, M; Kitamura, H; Kinugawa, T; Kobayashi, M; Kotake, H; Mashiba, H; Sato, R
Abstract : To evaluate purine degradation in patients with congestive heart failure concentrations of serum hypoxanthine, lactate, and noradrenaline were measured before and after submaximal treadmill exercise in 12 patients with chronic congestive heart failure and nine healthy volunteers. In four patients the concentration of hypoxanthine was significantly higher than in the controls or in the remaining eight patients with congestive heart failure. Venous lactate and noradrenaline in the four patients with high concentrations of hypoxanthine were also significantly higher than those in the eight patients with normal concentrations of hypoxanthine. Patients who responded normally were also more likely to have been treated with vasodilators and angiotensin converting enzyme inhibitors. Exercise induced arrhythmias were more common in the patients with high concentrations of hypoxanthine. These results suggest that the excess purine degradation in patients with congestive heart failure might be the result of a "relative" disturbance in the supply of adenosine triphosphate caused by the shift of cellular metabolism from aerobic glycolysis to anaerobic glycolysis during submaximal exercise and that hypoxanthine (a substrate for xanthine oxidase and a source of free radicals) was increased after submaximal exercise in some patients with congestive heart failure.